1995
DOI: 10.1159/000168880
|View full text |Cite
|
Sign up to set email alerts
|

Minimal-Change Nephrotic Syndrome Associated with Systemic Lupus Erythematosus

Abstract: A case of systemic lupus erythematosus (SLE) associated with minimal-change nephrotic syndrome (MCNS) is described. A 41-year-old woman with SLE presented with symptoms of nephrotic syndrome. Renal biopsy revealed minor glomerular abnormalities without the deposition of immune complexes. The initial heavy proteinuria promptly decreased after the prednisolone dosage was increased and disappeared 4 weeks later. The patient had a relapse of nephrotic syndrome without exacerbation of immunoserological reactions wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 11 publications
1
21
0
3
Order By: Relevance
“…Lupus podocytopathy was divided into three groups according to morphologic features: MCD (characterized by normal glomeruli or minimal MsP [4][5][6][7][8]), MsP ( defined as $3 mesangial cells per mesangial area [11][12][13][14]), or FSGS (at least one segmental solidification of the glomerular tuft with accumulation of extracellular matrix, hyalinosis and foam cells could be present). Collapsing FSGS was defined by the presence of segmental capillary tuft collapse in at least one glomerulus with overlying podocyte hyperplasia and/or hypertrophy (25).…”
Section: Renal Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…Lupus podocytopathy was divided into three groups according to morphologic features: MCD (characterized by normal glomeruli or minimal MsP [4][5][6][7][8]), MsP ( defined as $3 mesangial cells per mesangial area [11][12][13][14]), or FSGS (at least one segmental solidification of the glomerular tuft with accumulation of extracellular matrix, hyalinosis and foam cells could be present). Collapsing FSGS was defined by the presence of segmental capillary tuft collapse in at least one glomerulus with overlying podocyte hyperplasia and/or hypertrophy (25).…”
Section: Renal Morphologymentioning
confidence: 99%
“…NS is particularly characteristic of proliferative LN (class III, class IV) or membranous LN (class V) (1,2). However, it was observed 20 years ago that a subset of SLE patients who presented with NS were found to have normal glomeruli or only mild glomerular mesangial proliferation (3)(4)(5)(6)(7)(8). In these patients, the most prominent electron microscopy (EM) findings were diffuse foot process effacement (FPE) without immune deposits in the wall of peripheral capillaries, suggestive of podocytopathy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nephrotic syndrome or nephrotic range proteinuria in the context of SLE is often associated with identification of immune deposits in the glomerular capillary wall, with or without endocapillary proliferation and/or necrosis. However, there are reports of lupus patients who developed nephrotic syndrome in the absence of capillary wall immune deposits or cellular proliferation [3][4][5][6][7][8][9][10]. e lupus patient, who is described here, presented with nephrotic proteinuria with or without symptoms of nephrotic syndrome in four separate circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Makino et al [4] reported a case of minimal change nephritic syndrome associated with SLE and treated with methylprednisolone pulse therapy. Dube et al [5] reported on seven patients with SLE and minimal change disease treated with prednisone and cessation of NSAIDs.…”
Section: Discussionmentioning
confidence: 99%